OUTDOOR LEARNING SEBAGAI METODE PEMBELAJARAN IPS DALAM MENUMBUHKAN KARAKTER PEDULI LINGKUNGAN - Jakiatin Nisa (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
The world is increasingly rapid growth affect the level of competitiveness of each country in all sectors to conduct rapid national development and sustainable. However, the exploitation of the resources to open up the economy through infrastructure development, many did not heed the ability and capacity of the environment. Human resources play an important role in the process of success in maintaining, maintaining quality and environmental sustainability. Education is the most important element in the development system that can produce quality human resources. Through education (learning) that can foster environmentally conscious character, developing the potential of individuals (students) to be able to understand the importance of preserving the environment can be realized. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1339